Pola Komunikasi Pimpinan Dan Karyawan Dalam Pengembangan Iklim Komunikasi Organisasi Pada Probus System CV. Mitra Solusi Mandiri Denpasar - Gede Bagus, Anak Agung (Jurnal Kajian Ilmu Komunikasi, 2022)
In the research conducted, the authors wanted to know how the organizational communication patterns of leaders and employees in the development of organizational communication climate on the Probus System-CV. Mitra Solusi Mandiri Denpasar. This research uses a case study research design. The case study in this paper is to explore a fact, then provide an explanation regarding the various realities found. Therefore, the researcher directly observed the organizational communication process in the Probus System-CV. Mitra Solusi Mandiri in relation to the communication patterns of leaders and employees in developing the organizational communication climate. The approach used in this study is a qualitative approach. The data used through interviews, observation and documentation. Based on the results of data collection through interviews, the communication pattern in developing the communication climate, the organization refers to the aspects of the organizational communication climate as follows: 1) Trust, trust between leaders and their subordinates, the more accurate the exchange of information, the better understanding of performance goals and the quality of communication. growing taller. 2) Joint decision making, as a leader must involve employees in the decision-making process. Employees have equally important roles and responsibilities in order to produce an effective and quality decision for the company's organization. 3) Honesty, honesty itself must be owned by all people who do a job, because honesty is not only absolutely needed by employees to superiors, but bosses or bosses are also absolutely honest.